Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ases.12064
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic total remnant pancreatectomy after laparoscopic pancreaticoduodenectomy

Abstract: Total remnant pancreatectomy after pancreaticoduodenectomy (PD) is a difficult procedure. Recently, distal pancreatectomy and PD have been performed laparoscopically. Herein, we present the first case report of a laparoscopic total remnant pancreatectomy. A 72-year-old woman underwent a totally laparoscopic pylorus-preserving PD for inferior bile duct cancer. The tumor was composed of moderately differentiated tubular adenocarcinoma and was diagnosed as pStage III according to the UICC-TNM classification. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, in elderly patients who need to undergo pancreaticoduodenectomy, the mortality and morbidity rates were comparable between these two approaches, and LPD might have certain advantages over OPD (116). Similarly, several studies have also shown that LPD is safe and feasible in elderly patients (43,117,118). Topic 14: Follow-up after LPD Statement: Recurrence-free and overall survival after LPD are equal to that after OPD, and both procedures achieve equivalent rates of radical resection margins and number of harvested lymph nodes.…”
Section: Strength Of Recommendation: Strongmentioning
confidence: 99%
“…However, in elderly patients who need to undergo pancreaticoduodenectomy, the mortality and morbidity rates were comparable between these two approaches, and LPD might have certain advantages over OPD (116). Similarly, several studies have also shown that LPD is safe and feasible in elderly patients (43,117,118). Topic 14: Follow-up after LPD Statement: Recurrence-free and overall survival after LPD are equal to that after OPD, and both procedures achieve equivalent rates of radical resection margins and number of harvested lymph nodes.…”
Section: Strength Of Recommendation: Strongmentioning
confidence: 99%
“…Nonetheless, the minimally-invasive approach for CP has been rarely reported and to the best of our knowledge only 2 studies215 reporting on 3 cases have been published to date (Table 1). This is likely due to the combination of: 1) the rarity for the need of CP especially in the elective setting as isolated local recurrence of pancreatic neoplasms are rare and 2) the perceived technical difficulty of the procedure due to the frequent presence of dense adhesions occurring after PD.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the combination of: 1) the rarity for the need of CP especially in the elective setting as isolated local recurrence of pancreatic neoplasms are rare and 2) the perceived technical difficulty of the procedure due to the frequent presence of dense adhesions occurring after PD. Sunagawa et al reported the first laparoscopic CP after previous LPD in 2013 15. The patient developed remnant pancreatic cancer eighteen months after LPD for distal bile duct cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic pancreatectomy was first reported by Gagner and Pomp in 1994 , and since then, there has been a rapid increase in the number of papers reporting the effectiveness of this technique. Most of the reports cite reduced blood loss and shorter hospital stay as the main advantages of laparoscopic pancreatectomy . More recently, a number of meta‐analyses have compared Lap‐DP with laparotomy in terms of surgical outcomes .…”
Section: Discussionmentioning
confidence: 99%